Come see me and come lonely [compact disc] - Morgan, Lorrie; Tillis, Pam; Diffie, Joe; Worley, Darryl (Goldenlane Records, a division of Cleopatra, 2022)
Two queens of contemporary country music join forces on this powerful album, combining voices, vision, and talents to create one of the most exciting country releases.